Lower skeletal extension in Pleistocene Orbicella (Montastraea) corals than in their modern counterparts - Jordán-Garza, Adán Guillermo; Blanchon, Paul; Carricart-Ganivet, Juan P.; Jordán-Dahlgren, Eric (Frontiers in Marine Science, 2023)
Despite warmer conditions during the Last Interglacial, coral colonies of Orbicella were abundant and reached large sizes on many Caribbean reefs, including the extinct O. nancyi. To explore variation in growth rates, we examined the yearly mean linear extension of growth bands in two fossils Orbicella species and compared them with two modern species of the same genus from shallow waters of the wider Caribbean. We measured the linear extension on corals exposed in a fossil reef and modern counterparts, both in situ and from X-rays of coral slabs. Few coral colonies showed autocorrelation or a linear trend on their linear-growth time series. A Bayesian ANOVA showed lower linear-extension rates of fossils compared to modern samples and similar or lower than other fossil corals from Pleistocene locations. Growth rates and growth form significantly contribute to a coral colony's amount of tissue and size and can be a decisive trait for inter and intra specific competition. It is unlikely that temperature or interspecific competition explain modern coral extension rates and the low rates of the fossils data, which seem to be controlled instead by past habitat conditions.